PROBLEMS OF MODERN ORGANIC CHEMISTRY - Botirova Sayyora (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The science of chemistry is a science that deals with personnel, substances and bodies of all nature. Nature is a miracle, and there are a lot of mysteries that have not yet been opened it. That's the secret-Chemistry, Biology, Physical Sciences are very important for the opening of situations. In order to master these disciplines, students will need a lot of literature. But the issue of literature is now one of the most pressing problems. In order to overcome these problems, it is desirable to create a manual that is convenient for the students to use. Well, one of the urgent tasks is to translate the literature necessary for the students today into Uzbek, which is written in other languages, to create new ones.